A design-oriented model for FRP well-confined concrete cylinders under axial loading. (April 2022) - Ranjkesh Ghahnavieh, Mohammad; Kamgar, Reza; Heidarzadeh, Heisam
Abstract: The numerical studies on fiber-reinforced polymer (FRP) confined concretes are divided into two main groups. Analysis-oriented models implicitly predict the behavior of FRP-confined concrete concerning actively confined concrete models, and design-oriented models explicitly estimate the behavior of confined concrete using direct equations. After a short assessment of the proposed design-oriented models, this paper proposed and verified a new model based on experimental specimens and the previously published models. Results showed perfect accordance with the experimental results when all the required four main parameters (i.e., transition and ultimate stress and strains) were estimated accurately.